Superhydrophobic coatings for corrosion protection of magnesium alloys - Yao, Wenhui; Liang, Wu; Huang, Guangsheng; Jiang, Bin; Atrens, Andrej; Pan, Fusheng (Journal of materials science & technology, 2020)
Magnesium (Mg) alloys show great potential to be extensively applied in practice owing to their superior properties, while the poor corrosion resistance does undoubtedly restrict their applications. Superhydrophobic coatings with good repellency to corrosive solutions can significantly decrease the interaction between the corrosive species and the substrate, so that they are receiving a lot of attention to improve the corrosion resistance of Mg alloys. Various strategies have been introduced to develop a superhydrophobic coating on Mg alloys, which were reviewed to elucidate the current research status to provide a clue or thinking for beginning researchers. Further, the existing issues of superhydrophobic coating were discussed, especially for their real applications in practice, mainly owing to their poor mechanical stability. Based on the existing issues, the future study was discussed to improve the stability of hierarchical structures and entrapped air pockets, impart the superhydrophobic coating self-healing property to repair the damaged area during service, provide double protection by incorporation of corrosion inhibitors, or even introduce slippery liquid-infused porous surfaces with lubricant layer to provide better corrosion protection for Mg alloys.